The Light and the Heat: Productivity Co-Benefits of Energy-Saving Technology - Adhvaryu, Achyuta; Kala, Namrata; Nyshadham, Anant (The Review of Economics and Statistics, 2020)
We study the adoption of energy-efficient LED lighting in garment factories around Bangalore, India. Combining daily production line–level data with weather data, we estimate a negative, nonlinear productivity-temperature gradient. We find that LED lighting raises productivity on hot days. Using the firm's costs data, we estimate that the payback period for LED adoption is less than one-third the length after accounting for productivity co-benefits. The average factory in our data gains about $2,880 in power consumption savings and about $7,500 in productivity gains.